Retrospective Analysis Revealed an April Occurrence of Monkeypox in the Czech Republic - Chmel, Martin; Bartoš, Oldřich; Kabíčková, Hana; Pajer, Petr; Kubíčková, Pavla; Novotná, Iva; Bartovská, Zofia; Zlámal, Milan; Burantová, Anna; Holub, Michal; Jiřincová, Helena; Nagy, Alexander; et al. (Viruses, 2022)
Herein, we present our findings of an early appearance of the Monkeypox virus in Prague, Czech Republic. A retrospective analysis of biological samples, carried out on the 28th of April, revealed a previously unrecognized case of Monkeypox virus (MPxV) infection. Subsequent data analysis confirmed that the virus strain belongs to the ongoing outbreak. Combined with clinical and epidemiological investigations, we extended the roots of the current outbreak at least back to 16th of April, 2022.
Keywords: Česká republika; orthopoxvirus; Retrospective Studies; Monkeypox virus; epidemický výskyt choroby; infection; poxviridae; monkeypox virus; opičí neštovice; Disease Outbreaks; retrospektivní studie; Humans; zoonosis; outbreak; Czech Republic; Mpox, Monkeypox; lidé; virus opičích neštovic